2013
DOI: 10.1126/scitranslmed.3005145
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the JMJD2 Histone Demethylases to Epigenetically Control Herpesvirus Infection and Reactivation from Latency

Abstract: Chromatin and the chromatin modulation machinery not only provide a regulatory matrix for enabling cellular functions such as DNA replication and transcription but also regulate the infectious cycles of many DNA viruses. Elucidation of the components and mechanisms involved in this regulation is providing targets for the development of new antiviral therapies. Initiation of infection by herpes simplex virus (HSV) requires the activity of several cellular chromatin modification enzymes including the histone dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
149
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 98 publications
(152 citation statements)
references
References 50 publications
3
149
0
Order By: Relevance
“…Variations in transcription levels are associated with variations in mutation rates (55,56) and thus could be a confounding factor in the analysis, as could alterations of transcriptional kinetics. Relatedly, differences in histone association (57) and epigenetic silencing (58) alter transcriptional activity and may be associated with protein function. Changes in DNA biophysical properties that alter mutation potential, such as secondary structure (59), also cannot be excluded as possible contributors to the observed pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Variations in transcription levels are associated with variations in mutation rates (55,56) and thus could be a confounding factor in the analysis, as could alterations of transcriptional kinetics. Relatedly, differences in histone association (57) and epigenetic silencing (58) alter transcriptional activity and may be associated with protein function. Changes in DNA biophysical properties that alter mutation potential, such as secondary structure (59), also cannot be excluded as possible contributors to the observed pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, components of the cellular epigenetic machinery represent a plethora of novel therapeutic targets that can be used to modulate the expression of specific gene sets and alter the course of disease. Inhibitors of LSD1 and members of the JMJD2 family of histone H3K9 demethylases have been shown to suppress HSV infection and reactivation from latency (15)(16)(17)(18). In a contrasting approach, histone deacetylase inhibitors have been components of some strategies to induce HIV reactivation and deplete latent viral reservoirs (19)(20)(21).…”
mentioning
confidence: 99%
“…Upon infection of permissive cells, the HSV genome is assembled into chromatin structures that initially exhibit both H3K9me3 and H3K27me3 repressive histone methylation signatures (10,18,40,44,45). Initiation of lytic infection requires the recruitment of a cellular transcriptional coactivator complex (HCF-1) that contains histone H3K9 demethylases (LSD1, JMJD2s) and histone H3K4 methyltransferases (SETD1A, MLLs), which limits the accumulation of H3K9me3 and increases the levels of active H3K4me3 to promote the transcription of viral immediate-early (IE) genes (17,18,46). Similarly, the levels of H3K27me3 associated with the viral genome decrease over the course of productive infection in a manner dependent on IE protein ICP0 and viral DNA replication (40).…”
mentioning
confidence: 99%
“…It has been demonstrated that H3K9me2/3 demethylases (JMJD2s) and H3K9me1/2 demethylase LSDI reduce HSV-1 reactivation both in vitro and in vivo (20)(21)(22). It is difficult to state why inhibitors of the H3K9me2/me3 demethylases did not completely inhibit reactivation fully given issues with penetrance in the tissue and the experimental half-life of the drug.…”
mentioning
confidence: 99%